Efficient Host-Based Intrusion Detection for IoT Using Lightweight ML Models and Fuzzy Ranking - Uday H A; Arunalatha J S (International Journal of Scientific Research in Science and Technology, 2026)
The rising integration of IoT devices into various applications has amplified security risks, particularly in resource-limited setups with constrained computing capacity and storage. Standard intrusion detection approaches often prove inadequate for these contexts owing to their intensive resource needs. This work proposes a host-based intrusion detection system customized for IoT infrastructures, harnessing compact and adaptable machine learning strategies. The developed system examines diverse classifier groups, encompassing tree-oriented models like Decision Tree and Random Forest, boosting-oriented techniques such as LightGBM and XGBoost, support vector machines including LinearSVC, and linear-based classifiers encompassing Logistic Regression, Stochastic Gradient Descent, Passive-Aggressive methods, and Perceptron algorithms. To identify the optimal detection algorithms suited to varied IoT application environments, a multi-factor decision framework integrating TOPSIS, VIKOR, MOORA, and WASPAS ranking methodologies is utilized. Outcomes from trials reveal that linear classifiers and streamlined tree models deliver strong detection performance alongside brief training periods and lowered processing demands.The solution achieves a top accuracy rate of 98.7%, with training times under two seconds for the majority of algorithms, yielding roughly 15-20 times enhancement in efficiency relative to typical ensemble-driven intrusion detection systems.
Keywords: Internet of Things; Host-Based Intrusion Detection; Lightweight Machine Learning; Botnet Traffic Analysis; Fuzzy Decision-Making; CTU-13 Dataset